Case reportUrticaria vasculitis in the course of subacute cutaneous erythematosus – case report - Rosińska-Więckowicz, Anna; Misterska, Małgorzata; Żaba, Ryszard (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2009)
Subacute cutaneous lupus erythematosus (SCLE) is a non-scarring, non-atrophy-producing disease, with significant photosensitization. Even though during the course of the disease systemic symptoms are observed (subfebrile body temperature, myalgia, arthralgia), SCLE usually does not involve the kidneys. Furthermore, in some patients SCLE may be induced by drugs (antihypertensive agents, terbinafine). Urticarial vasculitis is a sort of chronic autoimmune urticaria resulting from vascular disorders, associated with immune complexes deposition and inflammatory cell infiltration around vessels (type III immune reaction according to the scheme of Gell and Coombs). Dissemination of urticarial wheals may be accompanied by arthralgia, myalgia and abdominal pain, and, very rarely, renal disturbances. Urticarial wheals take longer to resolve than is usually observed in urticaria – they are present up to 72 h. If urticarial vasculitis is suspected, a thorough examination should be carried out, directed towards connective tissue diseases (lupus erythematosus, hepatitis B and C) and deficiency of the second component complement. A case of a patient is presented in which hypersensitivity to ultraviolet radiation (MED 0.051 J/cm 2 ) provoked erythematous lesions on the face, trunk and upper limbs, accompanied by pruritus and arthralgia. Blood tests for anti-nuclear antibodies revealed high titres up to 1 : 2560. The patient presented typical symptoms of SCLE, but histological examination revealed characteristic alterations observed in urticarial vasculitis. After introduction of systemic treatment with methylprednisolone (16 mg/day) and dapsone (100 mg/day) both skin and systemic symptoms resolved, and remission of the disease is observed.